1993
DOI: 10.1007/bf00185869
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the trp repressor with trp operator DNA fragments

Abstract: The interaction of the trp repressor with several trp operator DNA fragments has been examined by DNA gel retardation assays and by circular dichroism, in the absence and presence of the corepressor L-tryptophan. The holorepressor binds stoichiometrically to both the trpO and aroH operators, forming 1:1 complexes. In the presence of excess protein, additional complexes are formed with these operator fragments. The relative electrophoretic mobilities of the 1:1 complexes differ significantly for trp and aroH op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thermodynamics and structural studies on the ATF-2 and 16mer/ATF-2 complex are currently in progress (M.R.Conte, G.Bloomberg and A.N.Lane, unpublished results), in order to investigate in detail the nature of the recognition process and to define the DNA conformation in the complex. DNA bends are often manifest in the 31 P NMR spectrum (57,58) or of the exchangeable protons (6). Preliminary 31 P and 1 H NMR results on the 16mer/ATF-2 complex (data not shown, M.R.Conte, G.Bloomberg and A.N.Lane, data to be published elsewhere) suggests that the DNA is not greatly distorted in the complex with ATF-2.…”
Section: Discussionmentioning
confidence: 91%
“…Thermodynamics and structural studies on the ATF-2 and 16mer/ATF-2 complex are currently in progress (M.R.Conte, G.Bloomberg and A.N.Lane, unpublished results), in order to investigate in detail the nature of the recognition process and to define the DNA conformation in the complex. DNA bends are often manifest in the 31 P NMR spectrum (57,58) or of the exchangeable protons (6). Preliminary 31 P and 1 H NMR results on the 16mer/ATF-2 complex (data not shown, M.R.Conte, G.Bloomberg and A.N.Lane, data to be published elsewhere) suggests that the DNA is not greatly distorted in the complex with ATF-2.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, there are four peaks upfield and two peaks downfield of the main group. The appearance of both upfield-and downfield-shifted 31 P NMR peaks in DNA-protein and DNA-ligand complexes has been observed in a number of systems (35)(36)(37). It has been suggested that these shifts are associated with changes in backbone torsion angles such as the B I to B II conformation transition (38) and other conformations (39,40).…”
Section: Determination Of the Minimal Dna-binding Domains Ofmentioning
confidence: 99%